A Study of the Determinants of Emissions Unit Allowance Price in the European Union Emissions Trading Scheme - Alina Maydybura; Brian Andrew (Australasian Accounting, Business and Finance Journal, 2012)
In 2005 the European Union (EU) began the first phase of the largest and most ambitious emissions trading system (EU ETS) ever attempted, which then applied to all members of the EU. In its second phase which began in 2008 the EU ETS now applies to all 27 members of the EU together with Norway, Iceland and Lichtenstein, the members of the European Economic Area (EEA) which are not members of the Union. In the first phase of the EU ETS permits to emit carbon into the atmosphere known as European Union Allowances (EUA) were traded in a market where the price rose to €30 and eventually fell to well below 10 Euro cents as the imperfections of the market became obvious. In the second phase which began in 2008 the price has fluctuated between €30 and €8. EUA are traded in a manner which is similar to the trading of financial instruments and a range of derivatives has developed with the total value of the market now above €120b, a growing market dominated by a few large players. This paper reports some results of an empirical investigation into the factors which appear to drive the carbon price and the key determinants of the price of an EUA. Over the last decade a number of environmental products have been developed alongside the EUA, including Certified Emissions Reductions (CERs), Renewable Energy Certificates and White Certificates (energy efficiency credits) and markets have developed for a range of these environmental products. A better understanding of the determinants of these markets will help regulators manage these new markets and this paper aims to enhance our knowledge of the market.
Keywords: era2015